Honing your knowledge skills - Funes, Mariana (New skills portfolio., 1998)
New technology and organizational structures are transforming the workplace, but management skills have not yet caught up. Harnessing knowledge and using it as a competitive advantage is one of the key priorities of organizations today. Honing Your Knowledge Skills looks at how to define knowledge working and identifies the practical skills of knowledge management needed by line managers. This book shows you how to *handle information overload *become an expert *harness new ideas *turn knowledge into action * keep knowledge skills fresh * understand IT resources and knowledge based systems The New Skills Portfolio is a groundbreaking new series, published in association with the Industrial Society, which re-defines the core management skills managers and team leaders need to be competitive. Each title is action-focused blending 20th century management initiatives/trends with a new flexible skills portfolio. The Industrial Society is one of the largest public training providers in the UK. It has over 10,000 member organisations and promotes best practice through its publishing, consultancy, training and advisory services. For more information contact their website on www.indsoc.co.uk Identifies practical knowledge skills Cutting edge themes Published in association with the Industrial Society.